Qualitative Phytochemical Analysis of Mamajjaka (Enicostemma Littorale Blume) (AYUSHDHARA, 2023)
The phytochemical analysis of plants plays a significant role commercially and has great interest in pharmaceutical companies for the manufacture of the new drugs to treat a variety of disorders. The Medicinal properties of a plant species lies in its phytochemical components that cause definite pharmacological action on the body. In the present study Mamajjaka (Enicostemma littorale Blume) was selected for qualitative phytochemical component analysis. The phytochemical analysis of aqueous and ethanolic extract samples was done to determine the phytochemical components in the plant. These extracts were used for qualitative phytochemical analysis using standard chemical tests. Results show the presence of various bioactive compounds such as carbohydrates, alkaloids, amino acids, protein, saponin, glycosides, phenolic compound, flavonoids, tannin and absence of steroids.